2019
DOI: 10.3389/fendo.2019.00269
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Involved in Childhood Obesity-Related Bone Fragility

Abstract: Childhood obesity is one of the major health problems in western countries. The excessive accumulation of adipose tissue causes inflammation, oxidative stress, apoptosis, and mitochondrial dysfunctions. Thus, obesity leads to the development of severe co-morbidities including type 2 diabetes mellitus, liver steatosis, cardiovascular, and neurodegenerative diseases which can develop early in life. Furthermore, obese children have low bone mineral density and a greater risk of osteoporosis and fractures. The kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 197 publications
0
40
0
Order By: Relevance
“…In obese children, Dimitri et al found a negative association between leptin and BMC (63) and between its unbound form and OPG (64,65). Leptin concentrations were inversely related to radial cortical porosity, radial cortical pore diameters, and tibial trabecular thickness (66).…”
Section: Excess Bmat and Inflammatory Cytokinesmentioning
confidence: 99%
“…In obese children, Dimitri et al found a negative association between leptin and BMC (63) and between its unbound form and OPG (64,65). Leptin concentrations were inversely related to radial cortical porosity, radial cortical pore diameters, and tibial trabecular thickness (66).…”
Section: Excess Bmat and Inflammatory Cytokinesmentioning
confidence: 99%
“…Indeed, compared to mature-leaf crops, they contain a higher amount of bioactive compounds, antioxidants, minerals, and phytonutrients [ 14 ]. Their consumption has been associated with a reduced risk of cancer, respiratory problems, osteoporosis, and muscle atrophy, which are frequent diseases associated with obesity and malnutrition [ 15 , 16 , 17 ]. Among these, Vigna radiata L. (mung bean) presents a high nutritional value of its sprouts, whose consumption has been related to antioxidant, anti-inflammatory, antidiabetic, antihypertensive, and antitumor effects [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Complementarily, low grade inflammation related to obesity promotes adipogenesis in the detriment of osteoblastogenesis and calcium absorption, increasing the risk of fractures and osteoporosis. [42][43][44] In a study presented by Ambroszkiewicz et al 45 higher CTX-I levels indicated a defective bone formation in thin children, compared to normal-weight peers. Moreover, the ratio of the carboxylated OC/undercarboxylated OC, as well as the BMD were significantly lower in thin children when compared to the normal-weight group.…”
Section: Predictive Roles Of Btms In Osteoporosis-related Pathologiesmentioning
confidence: 96%